PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO TELORINDO DI TANGERANG SELATAN - Damayanti, Nadia; Haryantini (Journal of Research and Publication Innovation, 2024)
This reseach purposed to investigate the influence of price and product quality, both partially and simultaneously, on purchasing decisions at the Telorindo Store, South Tangerang. The method used is quantitative. The sampling technique used the Slovin formula, with a sample size of 95 respondents. Data were collected using questionnaires, and data analysis techniques using validity, reliability, classical assumption tests, simple regression analysis, multiple regression multiple regression, hypothesis testing, t test, f test, and coefficient of determination. The results of this research show that partially price has a significant effect on purchasing decisions. This can be proven that tcount > ttable (5,110 > 1,987). From the results of simple linear regression analysis, the regression equation Y = 25,863 +0.516Χ1 The regression coefficient value obtained was 0.468, where the value was in the interval 0.400 – 0.599, meaning that the two variables had a moderate level of relationship And product quality has a significant influence on purchasing decisions. This can be proven by tcount>ttable (6,778 > 1,987). And the regression equation value Y = 18,924+ 0.567 This means that the two variables have a moderate level of relationship. Meanwhile, simultaneously price and product quality have a significant effect on purchasing decisions with the regression equation Y = 17,221 + 0.182X1 + 0.462X2, showing a (positive) influence. And the results of the hypothesis test obtained a value of f count > f table (24.382 > 3.10), while the results of the coefficient of determination were 0.346 or 34.6%. It can be concluded that the Price and Product Quality variables have a significant effect on the decision variable. Meanwhile, the remaining 65.4% was influenced by other factors that were not carried out by researchers.